Yugoslav communists towards Yugoslav idea and identity - Jagiełło–Szostak, Anna (Balcanica Posnaniensia. Acta et studia, 2013)
The aim of this article is to present the case of Yugoslav idea in the eyes of the Communist Party of Yugoslavia and a communist Yugoslav leader Josip Broz Tito and Edvard Kardelj. The author claims that special versions of the Yugoslav idea existed in Yugoslavia until 1964, when nationalisms raised and the federalization of the state started. After that, the Yugoslav state gained the name of the socialist community of the Yugoslav citizens not of the Yugoslav nation. In the article, the author investigates the speeches of J.B. Tito and the ideological opinion of the Communist Party of Yugoslavia until the eighties of the 20th century. After the death of Marshal Tito, one of the advocates of multinational Yugoslavia was Slobodan Milošević – the former president of the Republic of Serbia. He was a follower of the Yugoslav ideology created by J. B. Tito. Nowadays, Yugoslavia does not exist and the socialist idea of brotherhood and unity was replaced by national states and nationalism. It is worth to mention that the authors of book “Nebeska Jugoslavija”, M. Velikonja and V. Perica, promote “new Yugoslavism”, which is rather closer to Yugonostalgy and Yugosphere than to political ideology.